TIRE MEDIA TO IMPROVE JUMP SMASH SKIILS BADMINTON GAME UP - Gilang Ipen Sunyoto; Herman Tarigan; Candra Kurniawan (JUPE (Jurnal Penjaskesrek), 2019)
The purpose of this study was to determine the effect of tire rubber training on the results of smash jumps on badminton games, but the ability of smash jumps was still low. The method used is CAR (Class Action Research) through with as many as three cycles of research with 30 students. The technique of collecting data is a scale observation skill of smash jumping. The results of the study showed that in the first cycle, it is 72 of the calculation with effectiveness of 30.91% meant that the action had not been effective. In the second cycle, it is 77.33 with the calculation of the effectiveness of 40.6%; it means that the action has not been effective. In the third cycle, 92.67 with a calculation of effectiveness of 68.49%. The conclusion from the results of the study is that by using more rubber tire media it will be more effective, then the jump smash skill in the fifth grade of Tulung Agung 2 Elementary School, in the game of badminton increases.Tujuan penelitian ini adalah untuk mengetahui efektivitas latihan karet ban terhadap hasil smash loncat permainan bulutangkis masih rendahnya kemampuan smash loncat. Metode yang dipakai penelitian adalah PTK (Penelitian Tindakan Kelas) sebanyak tiga siklus subjek penelitian berjumlah 30 siswa. Teknik pengumpulan data menggunakan skala observasi keterampilan smash loncat. Hasil penelitian menunjukan pada siklus pertama sebesar 72 dengan perhitungan tingkat efektivitas 30,91 % yang berarti tindakan belum evektif. Pada siklus kedua sebesar 77,33 dengan perhitungan efektivitas 40,6 % itu berarti tindakan belum efektif. Pada siklus ketiga sebesar 92,67 dengan perhitungan efektivitas sebesar 68,49 %. Kesimpulan dari hasil penelitian tersebut bahwa dengan menggunakan media karet ban lebih banyak maka akan lebih efektif, maka keterampilan smash loncat pada kelas V SD Negeri 2 Tulung Agung, dalam permainan bulutangkis meningkat.Kata Kunci : Bulutangkis, Media Karet Ban, Permainan, Smash Loncat